Investigation of multilevel inverter for the next distributed generation using low-cost microcontroller - Zulkifli, Shamsul Aizam (Array, 2019)
Nowadays, more research projects have described a converter that is widely used at the distributed generation (DG) level in order to increase the amount of electrical power generation. The converter is known as an inverter when only one DG source is used or as a multi-inverter when several DGs are used. Here, the application of a multilevel inverter with a C2000 microcontroller (Texas Instruments (TI) TMS320F28335 microcontroller), which can be implemented with a current feedback loop, is investigated. This microcontroller acts as a communication interface between MATLAB SIMULINK and the multilevel inverter. Meanwhile, the current control model is modeled in MATLAB for designing the control strategy. It is where the multilevel inverter switches are triggered by using pulse-width modulation (PWM) signals generated by the microcontroller output. At the same time, the proportional integral derivative (PID) current control is used in order to allow the load current to follow the reference current. Based on the results, it can be summarized that the multilevel inverter is a very useful device for the next DG sources when it is combined with current control for load current distribution. From this investigation, it can be seen that in the future DGs could be connected to a multilevel inverter structure, where it will reduce the dependency on filter design and have a more sinusoidal output to the load for different DG power ratings.